A modified Dabestani-Mahan formula estimates a normal pulmonary artery systolic pressure: a single-center retrospective study. (14th October 2021) - Sunder, V; Cha, R; Hunter, K; Dolan, R; ,
Abstract: Background: Pulmonary artery systolic pressure (PASP) is increasingly used as an important datapoint in clinical decision-making and prognostication even in specialties outside of cardiology. Estimation of PASP by Doppler quantification using tricuspid regurgitation (TR) peak velocity is commonly used and correlates well with invasive measurement by right heart catheterization. Further study of transthoracic echocardiogram (TTE) techniques to estimate PASP is needed to provide this datapoint in the absence of sufficient Doppler data for the TR peak velocity method. One technique using right ventricular outflow tract acceleration time (AT) to estimate mean pulmonary artery pressure (MPAP) has been proposed by Dabestani Et al. by the equation MPAP=90-(0.62x AT). Assuming a linear relationship between MPAP and PASP, as suggested by Chemla Et al. by MPAP=(0.61xPASP)+2, a modified formula PASP=145-AT could possibly estimate a normal PASP ≤25 mmHg. Purpose: To examine if a modified Dabestani-Mahan formula PASP=145-AT can estimate a normal PASP ≤25 mmHg as calculated by the TR peak velocity method. Methods: We queried the electronic medical record at our institution for a sample of 300 patients who had a TTE performed between 2017 and 2020. Each TTE was reviewed and PASP was estimated for each using the TR peak velocity method. A right atrial pressure of 3 mmHg, 8 mmHg, or 15 mmHg was used in the estimation based on inferior vena cava diameter and collapsibility in keeping with the 2015 American Society of Echocardiography guidelines. A short axis view of pulmonary flow using the pulse-waved Doppler sample volume over the transpulmonary valve jet was then reviewed. The time from onset of ejection to peak flow velocity was measured manually as AT in milliseconds using Change Healthcare Cardiology Web Software Package 14.1.1. The measured AT was averaged over three cardiac cycles. Patients with a heart rate between 60 and 100 beats per minute at time of TTE and with sufficient Doppler data to estimate PASP by TR peak velocity and to measure AT were included in a logistic regression analysis. Results: 154 patients were included in the statistical analysis. Patients who had a right ventricular outflow tract acceleration time greater than 120 milliseconds, giving a PASP ≤25 mmHg by the modified formula PASP=145-AT, had a 36 times greater odds of having a PASP ≤25 mmHg by the TR peak velocity method (OR=36.0, 95% CI=10.36–125.12, p<0.001). Conclusion(s): Based on a single-center sample, a right ventricular outflow tract acceleration time greater than 120 milliseconds could be used to estimate a normal pulmonary artery systolic pressure less than or equal to 25 mmHg in the absence of sufficient Doppler data for the commonly used TR peak velocity method. Funding Acknowledgement: Type of funding sources: None.